Dynamics of Regional Government Policy Determination in Preparing Spatial Planning: Case in Banjarmasin City - Noor, Muhammad; Arbain, Taufik; Firdaus, Muhammad Riyandi; Setiawati, Budi (Universitas Muhammadiyah Malang, 2025)
This study analyzes the dynamics of local government policies that prioritize deliberative processes among various stakeholders to reach consensus in spatial planning in Banjarmasin City. This research collected and analyzed data using qualitative methodology. As this research shows, Banjarmasin City's spatial policy has experienced many dynamics. There are stakeholders who support and oppose local government policies. These stakeholder groups have interests that contribute to the failure of Banjarmasin City's spatial planning policies. This research definitely helps policy makers make better decisions. Among the stakeholders involved in decision-making, there are many perspectives to consider. Then, to avoid horizontal conflicts that are detrimental to the development process of an autonomous region, good cooperation among the various participating parties is required.